2022
DOI: 10.3389/fpsyg.2021.748321
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Parental Responsiveness, Teaching Responsiveness, and Creativity: The Mediating Role of Creative Self-Efficacy

Abstract: This study investigated the relationships between parental responsiveness, teaching responsiveness, and creativity, as well as the mechanism underlying these associations. We collected data from 584 Chinese college students via convenience sampling method and used self-report scales to measure their perceived parental responsiveness, teaching responsiveness, creative self-efficacy, and creativity. We employed structural equation modeling (SEM) to examine the relationships among these variables and the mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…As expected, the direct effects of creative self‐concept on creative behavior, creative self‐assessment, and positive affect were all significant. This is in line with previous studies that found individuals' creative self‐concept was positively related to their self‐reported innovative behaviors in both work and school contexts (Michael et al., 2011; Zhang et al., 2022; Zhang et al., 2021), and people with high levels of self‐concept were more likely to evaluate their creativity performance positively (Pretz & McCollum, 2014) and had a greater sense of positive affect and enjoyment (Intasao & Hao, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, the direct effects of creative self‐concept on creative behavior, creative self‐assessment, and positive affect were all significant. This is in line with previous studies that found individuals' creative self‐concept was positively related to their self‐reported innovative behaviors in both work and school contexts (Michael et al., 2011; Zhang et al., 2022; Zhang et al., 2021), and people with high levels of self‐concept were more likely to evaluate their creativity performance positively (Pretz & McCollum, 2014) and had a greater sense of positive affect and enjoyment (Intasao & Hao, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…(2011) also found that employees' creative self‐efficacy was positively related to their self‐reported innovative behaviors. Other studies in a university setting came to similar conclusions that creative self‐efficacy was a motivational factor for creative behavior and creative achievement (Zhang et al., 2022; Zhang et al., 2021). In these studies, creative self‐efficacy is trait‐like, stable and holistic, which matches the conception of creative self‐concept.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 63%
See 1 more Smart Citation
“…At the same time, Lin (1999) further defined creative expression as the use of all known information for a specific purpose to produce thinking results with distinctive, unique, social, or personal value, which can be new products, new processes, or new ideas. Technology can also be new ideas, new concepts, or new theories (Zhao et al, 2021;Zhang et al, 2022). This study followed the definition of creative expression in Lin (1999), and examined the learning effect of the integration of C-STEAM into a packaging design courses.…”
Section: Creativity Performancementioning
confidence: 99%
“…Research has pointed out that creative performance is an individual's comprehensive ability to generate new ideas, and discover and create new things. It is a necessary quality for successful creative activities (Li and Guo, 2018;Zhang et al, 2022). Based on the above reasons, this study focuses on the aspects of students' self-efficacy, student engagement, and creative performance to reflect learning effectiveness.…”
Section: Introductionmentioning
confidence: 99%